Reduction of plasma asymmetric dimethylarginine in obese patients with chronic kidney disease after three years of a low-protein diet supplemented with keto-amino acids: a randomized controlled trial - Teplan, Vladimir; Schück, Otto; Racek, Jaroslav; Mareckova, Olga; Stollova, Milena; Hanzal, Vladimir; Malý, Jan (Wiener klinische Wochenschrift, 2008)
BACKGROUND: Levels of the endogenous nitric oxide synthase inhibitor asymmetric dimethylarginine (ADMA) are elevated in chronic kidney disease (CKD) and may contribute to vascular complications. In this study we tested the hypothesis that elevated ADMA can be reduced in obese CKD patients by long-term administration of a low-protein diet supplemented with keto-amino acids. PATIENTS AND METHODS: In a long-term prospective double-blind placebo-controlled randomized trial, we evaluated for a period of 36 months a total of 111 CKD patients (54 men, 57 women) aged 22-76 years with obesity (BMI >or= 30 kg/m(2)) and an inulin clearance rate (C(in)) of 22-40 ml/min/1.73 m(2). All patients were on a low-protein diet containing 0.6 g protein/kg BW per day and 120-125 kJ/kg BW per day. The diet was randomly supplemented with keto-amino acids at a dosage of 100 mg/kg BW per day (66 patients, Group I); 65 patients received placebo (Group II). RESULTS: During the study period, the glomerular filtration rate decreased slightly in Group I (C(in) from 32.4 +/- 12.6 to 29.8 +/- 8.6 ml/min/1.73 m(2)) and more markedly in Group II (from 33.2 +/- 12.6 to 23.2 +/- 98.4 ml/min/1.73 m(2), P < 0.01). BMI decreased significantly in Group I (from 32.0 +/- 3.3 to 26.1 +/- 4.0 kg/m(2), P < 0.01) and was linked to reduced volume of visceral fat measured by MRI (P < 0.01). Reduction of BMI in Group II was not significant. In Group I, there was a significant decrease in the plasma level of ADMA (from 2.5 +/- 0.5 to 1.3 +/- 0.4 micromol/l, P < 0.01), but ADMA remained unchanged in Group II. A further remarkable finding in Group I was reduction in the plasma concentration of pentosidine (from 480 +/- 170 to 320 +/- 120 microg/l, P < 0.01) and decrease of proteinuria (from 3.8 +/- 2.24 to 1.6 +/- 1.0 g/24 h, P < 0.02). Plasma adiponectin rose in Group I (P < 0.01). Analysis of the lipid spectrum revealed a mild but significant decrease in total cholesterol and LPD-cholesterol (P < 0.02), more pronounced in Group I. There was also a decrease in plasma triglycerides in Group I (from 3.9 +/- 1.6 down to 2.2 +/- 0.6 mmol/l, P < 0.01) and a decrease in glycated hemoglobin (from 7.2 +/- 1.4% to 4.2 +/- 0.8%, P < 0.02). CONCLUSION: Compared with the placebo group, long term co-administration of a low-protein diet and keto-amino acids in CKD patients with obesity led to decreases of ADMA, visceral body fat and proteinuria. Concomitant decreases of glycated hemoglobin, LDL-cholesterol and pentosidine may also contribute to the delay in progression of renal failure.
Keywords: dospělí; Diet, Protein-Restricted; Female; chronické selhání ledvin; kombinovaná terapie; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; Arginine; Dietary Supplements; Obesity; lidé; nízkoproteinová dieta; potravní doplňky; Treatment Outcome; Kidney Failure, Chronic; obezita; Male; Combined Modality Therapy; Aged; Young Adult; arginin; Keto Acids; ketokyseliny; lidé středního věku; Amino Acids; senioři; mužské pohlaví; aminokyseliny; Middle Aged; Humans